Grain Boundary Complexions Enable a Simultaneous Optimization of Electron and Phonon Transport Leading to High‐Performance GeTe Thermoelectric Devices. Issue 3 (27th November 2022) - Zhang, Chaohua; Yan, Gan; Wang, Yibo; Wu, Xuelian; Hu, Lipeng; Liu, Fusheng; Ao, Weiqin; Cojocaru‐Mirédin, Oana; Wuttig, Matthias; Snyder, G. Jeffrey; Yu, Yuan
Abstract: Grain boundaries (GBs) form ubiquitous microstructures in polycrystalline materials which play a significant role in tuning the thermoelectric figure of merit ( ZT ). However, it is still unknown which types of GB features are beneficial for thermoelectrics due to the challenge of correlating complex GB microstructures with transport properties. Here, it is demonstrated that GB complexions formed by Ga segregation in GeTe‐based alloys can optimize electron and phonon transport simultaneously. The Ga‐rich complexions increase the power factor by reducing the GB resistivity with slightly improved Seebeck coefficients. Simultaneously, they lower the lattice thermal conductivity by strengthening the phonon scattering. In contrast, Ga2 Te3 precipitates at GBs act as barriers to scatter both phonons and electrons and are thus unable to improve ZT . Tailoring GBs combined with the beneficial alloying effects of Sb and Pb enables a peak ZT of ≈2.1 at 773 K and an average ZT of 1.3 within 300–723 K for Ge0.78 Ga0.01 Pb0.1 Sb0.07 Te. The corresponding thermoelectric device fabricated using 18‐pair p‐n legs shows a power density of 1.29 W cm −2 at a temperature difference of 476 K. This work indicates that GB complexions can be a facile way to optimize electron and phonon transport, further advancing thermoelectric materials. Abstract : Grain boundary complexions formed by Ga segregation optimize the electron and phonon transport simultaneously for enhancing the thermoelectric (TE) performance of GeTe‐based alloys. A peak ZT of ≈2.1 at 773 K can be obtained in Ge0.78 Ga0.01 Pb0.1 Sb0.07 Te, and a high power density of ≈1.29 W cm −2 under a temperature difference of 476 K can be achieved in an 18‐pair TE module.